Altmetrics is an indication of quality research or just HOT Topic - Wee, Joan Jee Foon (2015)
With the widespread use of social media tools in the discovery, dissemination and discussion of research output, altmetric measurements are fast gaining popularity and they supplement the traditional research metrics by tracking the number of social mentions of research articles. In recent years, there a few such tools and they adopt different models and have different coverage. Publishers such as Scopus and PLoS have already incorporated altmetrics in their websites. This paper seeks to make sense of these available tools and evaluate their effectiveness. Do they identify quality research or just HOT topics? This paper also analyses most cited papers from 18 different subject categories in Web of Science (WOS) and compares the results with an altmetrics database to find out the correlation between these 2 sets of data. This paper ends by highlighting how users could leverage altmetrics effectively to disseminate their works to a wider audience.